Teledentistry: A Boon in Indian Scenario - Kallury, Amitabh; Jain, Ankur; Agrawal, Kunal; Sahu, Aishwarya; Saluja, Sheena; Mahajan, Anurag (Journal of Orofacial Research, 2019)
An amalgamation of telecommunication and dentistry is known as ‘Teledentistry’, which involves switch over the clinical information in remote areas for diagnosis, consultation, health education and treatment planning. The accessibility of dental care at low cost by all people has ton increased by teledentistry. It also has an immense perspective to overcome the disparities in oral healthcare between rural and urban population. Thus the aim behind to review this article is to establish the essential role of Teledentistry in Indian Scenari. The literature for this review obtained from published articles, online manuals and books.